Relational styles for solving difficult situations in an employee team = Style relacyjne rozwiązywania sytuacji trudnych w zespole pracowniczym - Rongińska, Tatiana; Doliński, Artur (Zielona Góra: Faculty of Economics and Management Press)
The article proposes the inclusion of relational styles of managers in difficult situations occurring in an employee team. Four types of relational styles have been distinguished: partner, handler, buddy and coach. The research covered 261 middle and senior managers of one of large corporations in Poland. The research was carried out for two years during the training contract. The article presents the results of relational style research at the training stage, which allowed to diagnose the relational style of the surveyed managers.
Keywords: zespół pracowniczy; sytuacja trudna; granice zachowań; styl relacyjny; bliskość relacyjna; dystans relacyjny; employee team; difficult situation; boundaries of behaviour; relational style; relational closeness; elational distance